Pengaruh Celebrity Endorsement terhadap Purchase Intention melalui Brand Image sebagai Variabel Intervening - Megayani Megayani; Ellen Marlina (Jurnal Manajemen, 2019)
The research purpose is to analyzed impact celebrity endorsement to purchase intention throught brand image as intervening variable on Geprek Ayam Bensu in East Jakarta. The strategy research used explanatory research and association research. The population is customers Geprek Ayam Bensu in East Jakarta and using sample as much 117 respondent. Method used quantitative research. The analyzing technique use structural equation modeling analysis. The result research is: (1) celebrity endorsement not have impact significant to purchase intention. (2) brand image have impact significant to purchase intention. (3) celebrity endorsement have impact significant to brand image.